PEMBERDAYAAN DESTANA DALAM MENGEMBANGKAN POTENSI DESA SIAGA BENCANA BERBASIS MASYARAKAT - Sri Wahyuni Adriani; Zuhrotul Eka Yulis Anggraeni; Natasya Carla Aprilia; Fizal Afandi (Universitas Muhammadiyah Tapanuli Selatan, 2022)
Panti Village is a flood-prone area because of its geographical location in a watershed. In addition, in 2006 the flood disaster that hit the sub-district caused severe damage and loss of life as well as serious health problems, especially in Suci Village. This condition causes Suci Village to be a disaster-prone village so that it is always prepared, especially during the rainy season. But on the other hand, community preparedness is still low. If this condition is not addressed, it will have an impact on the problems that arise when a flood occurs. This problem requires management through the empowerment of Destana (Disaster Responsibility Village). The method used in solving problems was through screening of groups vulnerable to disasters, discussions to map disaster-prone areas, education and simulations through disaster TRIAGE training and mentoring. The results show that the number of vulnerable groups was 87 pregnant women, 816 children under five, 571 elderly people, and 37 people with disabilities. For mapping disaster-prone areas, it was known that all hamlets in Suci Village are classified as disaster-prone, namely Glengseran, Gaplek, and Glundengan. As for Destana training, it is known that there has been an increase in knowledge about disaster preparedness from 70% enough to 80% having good knowledge, as well as TRIAGE skills, an increase from 70% good knowledge to 85% good knowledge. Education, training, and mentoring activities as a form of Destana empowerment were effective as one of the strategies in developing disaster preparedness villages.